A review of medicinal, chemical, and pharmacological properties of Cissus cornifolia (Baker) Planch. (Vitaceae family) - Alfred Maroyi (Journal of Applied Pharmaceutical Science, 2025)
Cissus cornifolia (Baker) Planch. is a scandent shrub used as food and traditional medicine in tropical Africa. The present review compiles existing information on the medicinal uses, chemical, and pharmacological properties of C. cornifolia. Literature searches on the traditional, medicinal, phytochemistry, and biological activities of C. cornifolia were conducted using online databases which included Web of Science, Google Scholar, Scopus®, SpringerLink®, ScienceDirect®, SciELO, and PubMed®, as well as using pre-electronic literature sources obtained from the university library. The current study showed that fruits, bark, leaf sap, leaves, root bark, roots, rootstock, stem bark, and twigs of C. cornifolia are used against 33 human and animal ailments and diseases. The chemical evaluation of the plant revealed that it contains alkaloids, alkanes, methyl esters, steroids, triterpenoids, organo heterosilane, prenylated benzo-lactone, cardiac glycosides, catechol, coumarins, flavonoids, fatty acids, phenolics, dicarboxylic acid, saponins, terpenoids, and tannins. Ethnopharmacological evaluations showed that the crude extracts and chemical compounds isolated from the species have antifungal, antibacterial, anticonvulsant, anti-diabetic, antidiarrhoeal, anti-inflammatory, antioxidant, antiproliferative, central nervous system depressant, nematicidal and neuropharmacological activities. Detailed studies focusing on toxicological evaluations, in vivo studies, and clinical assessments aimed at corroborating the documented traditional medical uses of C. cornifolia are recommended.
Keywords: Cissus cornifolia, grape, materia medica, traditional medicine, tropical Africa, Vitaceae